The doctrine of reception - Eishan Jan, Mohammad Naqib (The Malaysian Current Law Journal Sdn Bhd, 2014)
This chapter basically explains the concept of reception that was devised and used by the British Empire to explain the introduction and application of its laws into the territories which it colonized. During the 17th – to early 20th centuries British Empire, following an expansionist policy, colonized Americas and most of the countries in Asia and Africa, plundered the raw materials in these territories which were in high demand in the era of Europe’s Industrial Revolution, enriched itself at the expense of other nations’ right to self-determination, proclaimed itself as the lord of the newly acquired territories , subjugated other people , brought European ideas, introduced its language and most importantly paved the way in the colonized territories for the reception of its laws. The colonization of other nations’ territories by the British colonial power effectuated within the purview of ancient international law through the modes of ‘conquest’, ‘cession’ or ‘occupation. Cession and occupation are still recognized as modes of acquisition of territory in contemporary international law – a law that governs, inter alia, the relations among states. The chapter also explain the modes of acquisition of territories in international law and try to link them with the doctrine of reception.